2008
DOI: 10.1080/13693780802140907
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 and its role in antifungal immunity

Abstract: The innate recognition of fungal pathogens is mediated by a variety of pattern recognition receptors (PRRs), although much interest has focussed on the Toll-like Receptors (TLR). More recently, however, there is growing appreciation that the non-TLRs have a major role in the control of infection with these organisms. One such molecule is Dectin-1, a C-type lectin-like receptor which induces numerous cellular responses upon recognition of fungal beta-glucans. Here we review our current understanding of the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 72 publications
2
34
0
Order By: Relevance
“…Our data are in agreement with other studies demonstrating that Dectin-1 recognizes particulate and soluble ␤-glucan (27) for a number of fungal species (36). Our results demonstrating that ␤ 2 -integrin, TLR2, and Dectin-1 are required for Hc, F1,and ␤-glucan recognition and LB formation suggest that a complex interaction occurs between fungi and cells from the immune system and that this interaction appears to be necessary for signaling to take place.…”
Section: Discussionsupporting
confidence: 83%
“…Our data are in agreement with other studies demonstrating that Dectin-1 recognizes particulate and soluble ␤-glucan (27) for a number of fungal species (36). Our results demonstrating that ␤ 2 -integrin, TLR2, and Dectin-1 are required for Hc, F1,and ␤-glucan recognition and LB formation suggest that a complex interaction occurs between fungi and cells from the immune system and that this interaction appears to be necessary for signaling to take place.…”
Section: Discussionsupporting
confidence: 83%
“…These studies identified numerous host PRRs, including Dectin-1, mannose receptor, and CD11b, that were involved in mediating phagocytosis (7). Interactions between the host PRR Dectin-1 and fungal PAMP ␤-(1,3)-glucan were shown to be particularly important for host defense against a variety of pathogenic fungi (7,25,28). We confirmed that ␤-(1,3)-glucan was accessible on the surface of C. neoformans spores (Fig.…”
Section: Resultssupporting
confidence: 66%
“…The studies reported herein demonstrate that the major markers of macrophage activation can be categorized as early (maximum at 6 h) or late (evident at 24 h) and their Similarly, the mannose and dectin-1 receptors are involved in the recognition of mannose residues on pathogens [20] and b-glucans on fungal pathogens [32][33][34], respectively, and are early markers of alternative activation. In contrast, the ym1 and fizz1 gene products, chitnase [48] and resistinlike proteins [49], respectively, that are involved in wound healing and tissue repair are late markers of alternative activation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, alternative activation has been associated with arginase 1, fizz1 and ym1 that are involved in tissue repair, control of some parasitic infections and control of reactive nitrogen intermediates [6,7,10,27,29,30]. However, these macrophages are also associated with the expression of the mannose receptor [3] and dectin-1 [4], which are important in pathogen recognition and have been demonstrated to play a beneficial role in fungal infections [31][32][33][34][35]. More recently it has been suggested that activated macrophages comprise a spectrum based on three major activities; classically activated (as described previously), wound-healing (stimulated with IL-4 or IL-13) and regulatory, which are induced by TLR ligation in combination with other stimuli, including immune complexes [21].…”
Section: Discussionmentioning
confidence: 99%